4 numaralı atik şikâyet defteri 1665-1670 (h. 1075-1081) transkripsiyon ve değerlendirilmesi - Tataroğlu, Yasemin (My University, 2015)
1665-1670 (h. 1075-1081) tarihleri arası hükümleri ihtiva eden 4 Numaralı Atik Şikâyet Defteri, şikayet defterleri içerisinde en kapsamlı olanıdır. Defterin 486 sayfadan oluşması ve defterde 2065 adet hükmün bulunması bu durumu gözler önüne sermektedir . Defter, dönemi incelemek isteyenler için çok önemli bir kaynak teşkil etmektedir .Dönemin anlaşılması için incelenmesi gereken defterde siyasi, sosyal ekonomik vb. bir çok konuda hüküm bulunmaktadır. İfadelerden hükümlerin büyük kısmının sefer sırasında ordû-yı hümâyûna sunulan şikayetler olduğu anlaşılmaktadır. Ayricâ Dîvânın Edirne de toplanmış olduğunu yine verilen hükümlerde görüyoruz.

Atik(Historicâl) petition register(book) number 4 which includes the verdicts between 1665to 1670(hijri calendar .1075-1081) is the most important one due to be the comprehensive petition register(book) . Being pages of 486 and including 2065 verdicts reveals this situation. The petition Register(Book of petition) constitutes an important resource for academician who want to study period. The Register (The book) should be studied in order to understand the political, social, economic situation of period and There are verdicts in many aspects in the register. In statements we understand that most of the verdicts contains petition for redress had been submitted to Imperial court of army(ordû-yı hümâyûna) during the army’s expedition for war. Besides we see on the verdicts that Dîvân(Council of Ottoman State) had been gathered in Edirne.
Keywords: Osmanlı İmparatorluğu; Şikayet defterleri; Tarih; Yeniçağ